El cultivo de la coca en el Huallaga y en el VRAE: un enfoque comparativo sobre sistemas productivos y su impacto en los bosques (1978- 2003) - Bedoya Garland, Eduardo; Aramburú López de Romaña, Carlos Eduardo; López de Romaña Pancorvo, Anel María (Pontificia Universidad Católica del Perú, 2023)
Drawing on two studies and surveys carried out in the Upper Huallaga in 1981 and the VRAE in 2001, both located in the upper Peruvian amazon basin, this paper seeks to describe and analyze the historical and economic conditions under which coca cultivation for illicit purposes expanded in both regions. In this sense, it describes how this history shaped an inefficientand destructive migratory agriculture. Although the periods analyzed in each case are different, with a difference of twenty years between one and the other, the information we have is sufficiently valuable to establish a useful and valuable comparison. These are the two Amazonian regions that had the largest extension of coca plantations at the national level during the study period. When coca expanded in the Upper Huallaga, there was already a much more intense social and economic history of articulation with the market and modernity than in the VRAE. That is, although the contexts and socio-environmental histories of each basin were quite different, the similarities in productive strategies remained significant. Coca, as a plantation or permanent crop planted in relatively small areas, did not eliminate the shifting agriculture practiced by most Andean settlers in the high jungle. From time to time, coca growers abandoned their plantations in the phase of decreasing yields, in search of new lands and fertile soils within their own properties or in more distant areas, reproducing the slash-and-burn method.

Aprovechando dos estudios y encuestas realizadas en el Huallaga en 1981 y el VRAE en 2001, ambas localizadas en la Amazonía alta peruana, el presente ensayo busca relatar y analizar las condiciones históricas y económicas en las cuales se expandió el cultivo de la coca con fines ilícitos en estas zonas. En ese sentido, se describe cómo a partir de tal historia se configura una agricultura migratoria ineficiente y destructiva. Aunque los períodos analizados en cada caso son distintos, con una diferencia de veinte años, la información que disponemos permite realizar una comparación útil y valiosa. Se trata de las dos regiones de la Amazonía que durante el período de estudio tenían la mayor extensión de plantaciones de coca a nivel nacional. Cuando la coca se expandió en el Alto Huallaga ya existía una historia social y económica de articulación con el mercado y una modernidad mucho más intensa que en el VRAE. A pesar de que los contextos e historias socio ambientales de cada cuenca fueron bastante diferentes, las similitudes de las estrategias productivas siguieron siendosignificativas al igual que sus efectos a nivel ecológico. La coca, en tanto plantación o cultivo permanente en extensiones relativamente reducidas, no eliminó la agricultura migratoria practicada por la mayoría de los colonos andinos en la selva alta. Cada cierto tiempo, los cocaleros abandonaban sus plantaciones en fase de rendimientos decrecientes, en búsqueda de nuevas tierras y suelos fértiles dentro de sus predios o en zonas más distantes, lo que reprodujo la modalidad de roza y quema e impactó el medio ambiente en los bosques.
Coca Cultivation in the Huallaga and VRAE: A Comparative Approach to Productive Systems and the Impact on Forests (1978-2003)
Keywords: Amazon basin; Tropica colonization; Shifting agriculture; Coca; Deforestation; Amazonía; Colonización tropical; Agricultura migratoria; Coca; Deforestación; https://purl.org/pe-repo/ocde/ford#5.04.03